Microscopy using randomized speckle illumination - Perinchery, Sandeep Menon (2019)
It is well known for structured illumination microscopy (SIM) that the lateral resolution by a factor of two beyond the classical diffraction limit is achieved using spatially structured illumination in wide-field fluorescence microscope. In the state of art SIM systems, grating patterns are generally generated by physical gratings or by spatial light modulators such as digital micro mirrors (DMD), liquid crystal displays (LCD). In this study, using a combination of LCD and ground glasses, size controlled randomized speckle patterns are generated as an illumination source for the microscope. Proof of concept of using speckle illumination in SIM configuration is tested by imaging fixed BPAE cells.